Meningkatkan Kompetensi Guru melalui Pelatihan Penulisan Karya Ilmiah di SMAN 1 Kayu Agung Kabupaten Ogan Komering Ilir - Tri Widayatsih; Nurlina Nurlina; Edi Harapan; Suherman Suherman; Hery Setyo Nugroho; Muhammad Fahmi; Pahlawan Pahlawan; Nuril Furqon; Akbariansyah Akbariansyah; Yudi Irwansi (Lembaga Pengembangan Kinerja Dosen, 2026)
The limited ability of teachers to write scientific papers remains one of the obstacles to professional development and career advancement. This activity aimed to improve teachers’ competencies through scientific writing training at SMAN 1 Kayu Agung, Ogan Komering Ilir Regency. The method employed was training and mentoring, which included the delivery of materials on basic concepts of scientific writing, the structure of scientific articles, citation and referencing techniques, and practical sessions on preparing scientific articles. The participants of this activity were teachers of SMAN 1 Kayu Agung. The results showed an improvement in teachers’ understanding and skills in writing scientific papers, as indicated by their ability to produce scientific articles in accordance with proper academic writing standards. In addition, teachers demonstrated positive attitudes and increased motivation to produce scientific works as part of continuous professional development. Therefore, scientific writing training is effective in enhancing teachers’ competencies and can serve as a strategy for teacher professional development in schools.